Plant-Derived Antimicrobial Agents: A Promising Solution to Combat Multidrug Resistance - Kumari, Jyoti; Sharma, Niharika; Kumari, Shikha (Journal of Neonatal Surgery, 2025)
Multidrug resistance (MDR) has emerged as a major global health threat, compromising the effectiveness of conventional treatment therapies and leading to increased morbidity, and mortality. The indiscriminate utilization of antibiotics in human healthcare, agriculture, and veterinary practices has enhanced the development and transmission of antibiotic resistant strains. In response to this alarming condition, there has been a renewed interest in alternative antimicrobial agents, particularly from compounds derived from plants. Medicinal plants are utilized in traditional medicine for many years and offer a promising source of bioactive molecules capable of combating resistant pathogens. Phytochemicals, such as terpenes, alkaloids, flavonoids, and polyphenols have demonstrated significant antimicrobial activity, acting through mechanisms such as membrane disruption, efflux pump inhibition, and enzyme inhibition. This review explores the growing challenge of MDR infections, detailing the mechanisms through which microbes evade antimicrobial agents and role of plant based compounds in fighting drug resistance. Moreover, it discusses the challenges associated with combating multi drug infections and development of novel antimicrobial agents from plants. Despite these challenges, plant-derived antimicrobials offer a promising pathway for developing innovative strategies to combat multidrug resistant (MDR) infections and tackle the escalating threat of antibiotic resistance.